RIGS16-176-0340/The studies on environmentally safe biopolymer derived from natural based algae - Othman, Maizatulnisa; Mohamad, Souad A.; Jamal, Nur Ayuni Jamal (2017)
In the efforts to sustain the environment, biodegradable plastic has become a great alternative to replace conventional plastic. Hence, this study focuses on a potential biodegradable plastic. In the current study, the properties of algae (matrix) were investigated by adding acetic acid and cinnamon powder as filler and antimicrobial agent. The amount of acetic acid varies from 0.1, 0.3 and 0.5%, while, the cinnamon content between 1, 3 and 5%. The film was fabricated using the solution casting method. Upon fabrication, the physical and mechanical properties of the films were characterized using tensile test, Fourier Transform Infrared Spectrometry (FTIR) analysis, Scanning Electron Microscopy (SEM) analysis and biodegradation test. Based on the results, the addition of acetic acid and cinnamon are capable of affecting the tensile property of the algae film. Initially, it indicated that the acetic acid reduced the tensile property and affected the elongation at break of the algae film. However, the tensile strength of the film was altered by adding a certain amount of cinnamon. The maximum tensile strength was achieved by the addition of 5% cinnamon which exhibited a good intermolecular interaction between the algae and cinnamon molecules. The tensile strength which was measured at 4.80 MPa correlated with the morphological structure. The latter was performed using SEM, where, the surface showed the absence of a separating phase between the algae and cinnamon blend. Moreover, the addition of acetic acid into the algae film clearly indicated that the acetic acid molecules affect the adjacent molecules by increasing the distance and reducing the internal force giving more flexibility to the film. This was evidenced by the Fourier Transform Infrared (FTIR) analysis which confirmed the occurrence of no chemical reaction between the algae and acetic acid. The C-H stretching due to the formation of intermolecular and intramolecular bonds between algae and carboxylic acid groups corresponds to the water-related absorbance. As for the biodegradable analysis, the addition of acetic acid into cinnamon, demonstrated low moisture absorption thus decelerating the degradation due to low swelling rate and microorganism activity. In conclusion, good tensile properties and longer degradation rate are achievable with the addition of 0.3% of acidic acid with 5% of cinnamon blended with the algae matrix.